An Interactive SAR Approach to Discover Novel Hybrid Thieno Probes as Ligands for D2‐Like Receptors with Affinities in the Subnanomolar Range. Issue 12 (December 2013) - Abdel‐Fattah, Mohamed A. O.; Lehmann, Jochen; Abadi, Ashraf H.
Abstract A series of [(phenylpiperazinyl)alkyl]‐isoindole‐1, 3‐dione derivatives was synthesized to serve as probes for dopaminergic receptors. Among this series, compound 6a showed the highest affinity towards D4 and D3 receptors with Ki values in the low nanomolar range, and D2/D4‐ and D2/D3‐selectivity indices of 72 and 20, respectively. Optimization rounds were adopted and led to the D4‐selective ligand thiophene‐2‐carboxamide 9a with a Ki(D4) value of 0.62 nM, and to its butyl analog, 10a, with Ki(D4) and Ki(D3) values of 0.03 and 0.26 nM, respectively. Docking experiments revealed the importance of the unique D4 residue Arg186 in manipulating the ligands' D4‐subtype‐receptor selectivity.